Analysis of Factors that Affect the Production of Rice Paddy Farming in Lupia Village of Kabangka Sub District Muna District - Meiliawati, Wa Ode Chris; Pandangaran, Ayub Manggala; Dirgantoro, Muhammad Arief (International Journal of Agricultural Social Economics and Rural Development (Ijaserd), 2021)
This study aims to analyze the factors that influence the production obtained from rice farming in Lupia Village, Kabangka District, Muna Regency. This research was conducted in Lupia Village, Kabangka District, Muna Regency. There were 42 respondents, conducted using the simple random sampling method (simple random sampling) using the Slovin formula. The data analysis used was Cobb-Douglas analysis. The results showed that the variables of land area, seeds, and pesticides had a significant effect on rice production, while labor, urea fertilizer, and NPK Phonska fertilizer did not have a significant effect on rice production in Lupia Village, Kabangka District, Muna Regency.